Leveraging Biomaterial Mechanics to Improve Pluripotent Stem Cell Applications for Tissue Engineering - Lenzini, Stephen; Devine, Daniel; Shin, Jae-Won (Frontiers in Bioengineering and Biotechnology, 2019)
A primary goal in tissue engineering is to develop functional tissues by recapitulating salient features of complex biological systems that exhibit a diverse range of physical forces. Induced pluripotent stem cells are promising autologous cell sources to execute these developmental programs and their functions; however, cells require an extracellular environment where they will sense and respond to mechanical forces. Thus, understanding the biophysical relationships between stem cells and their extracellular environments will improve the ability to design complex biological systems through tissue engineering. This article first describes how the mechanical properties of the environment are important determinants of developmental processes, and then further details how biomaterials can be designed to precisely control the mechanics of cell-matrix interactions in order to study and define their reprogramming, self-renewal, differentiation, and morphogenesis. Finally, a perspective is presented on how insights from the mechanics of cell-matrix interactions can be leveraged to control pluripotent stem cells for tissue engineering applications.